1996
DOI: 10.1144/gsjgs.153.3.0375
|View full text |Cite
|
Sign up to set email alerts
|

Strike-slip deformation in the Confidence Hills, southern Death Valley fault zone, eastern California, USA

Abstract: The Confidence Hills form a well exposed, composite, positive flower structure developed in Pliocene to Recent lacustrine and alluvial fan sediments. The structure has developed along the current trace of the southern Death Valley dextral strike-slip fault zone. California, USA. NW-SEstriking fault zones bound the Confidence Hills. In 3D, these fault segments are inferred to link at depth to a common basal fault system. The flower structure is formed by doubly plunging anticlines that roughly parallel the boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…Such flower structure development is a common characteristic in the formation of strikeslip fault systems and does not require restraining oversteps or transpressional strain (e.g. Dooley & McClay 1996).…”
Section: Fault Architecture Of the Saiina Del Fraile Pull-apart Basinmentioning
confidence: 99%
“…Such flower structure development is a common characteristic in the formation of strikeslip fault systems and does not require restraining oversteps or transpressional strain (e.g. Dooley & McClay 1996).…”
Section: Fault Architecture Of the Saiina Del Fraile Pull-apart Basinmentioning
confidence: 99%
“…Previous studies suggest that complex surface faulting may become simpler at depth as faults coalesce onto prominent structures, so-called flower structures [Weldon II et al, 2002;Bozkurt and Koçyiôit, 1996;Wei et al, 2011]. Active flower structures have been observed along major well-developed strike-slip fault systems such as the southern San Andreas fault [Weldon II et al, 2002], along other major strike-slip fault systems in Southern California [Harding, 1985[Harding, , 1988Dooley and McClay, 1996], and along the North Anatolian fault [Bozkurt and Koçyiôit, 1996]. Conversely, it has also been shown that highly active, immature strike-slip fault systems may consist of parallel throughgoing fault strands, with secondary splays at varying orientations [Rybicki, 1973;Segall and Pollard, 1980;Reasenberg and Ellsworth, 1982].…”
Section: Introductionmentioning
confidence: 99%
“…Like the Black Mountains sections, these sediments show little evidence of syndepositional tec tonism, yet are now highly deformed, with almost vertical dips in places (Beratan et al, 1999). This deformation is associated with the Southern Death Valley strike-slip fault (Dooley and McClay, 1996) and gives a qualitative indication of the large amount of post-1.7 Ma motion there has been on this fault.…”
Section: Geologic Framework Of the Death Valley Regionmentioning
confidence: 93%